Preparation method of high-resilience graphene foaming film

By adjusting the mixed solvent composition of the reducing agent and controlling the immersion and drying process of the graphene oxide film, a graphene foam film with narrow pore size distribution and small average pore size was prepared, which solved the problem of insufficient compression resilience of the graphene foam film in traditional processes, significantly improved the compression resistance and resilience of the material, and improved the thermal conductivity.

CN119551666AActive Publication Date: 2025-03-04ZHEJIANG ENJIE THERMAL MANAGEMENT TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510116110.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-03-04
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

Traditional preparation processes are difficult to improve the compression resilience performance of graphene foam film, and the uneven pore size distribution leads to insufficient overall performance of the material.

Method used

By adjusting the composition of the mixed solvent of the reducing agent, tert-butanol and hydrazine hydrate are dissolved in the mixed solvent, the immersion and drying process of the graphene oxide film is controlled to form a graphene foam film with narrow pore size distribution and small average pore size.

Benefits of technology

It significantly improves the compression resilience performance of the graphene foam film, forms a fine pore structure, improves the compression resistance and resilience of the material, and improves the conductivity and thermal conductivity in the vertical direction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551666A_ABST
    Figure CN119551666A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-resilience graphene foamed film, which is characterized in that on the basis of traditional hydrazine hydrate foaming, tert-butyl alcohol is introduced as a regulator, so that the problem of non-uniform pore size distribution in a graphene film caused by rapid reduction of hydrazine hydrate is avoided, and the compression resistance and resilience of the whole material are improved by virtue of a fine pore structure. And through subsequent low-temperature thermal reduction, carbonization and graphitization treatment, the conjugated structure of the graphene is further recovered, and the porous membrane skeleton is endowed with high compression resilience performance. The obtained high-resilience foaming film can be used as a base material of materials for phase change heat storage, batteries, capacitors, thermal interfaces and the like, and preparation of a high-mechanical-property composite material is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of graphene films, in particular to a method for preparing a high-resilience graphene foam film. Background Art

[0002] Graphene, a two-dimensional carbon nanomaterial, demonstrates broad application potential across multiple fields due to its exceptional physical and chemical properties. Its high surface area, high Young's modulus, high electron mobility, and excellent thermal conductivity have led to widespread interest in key areas such as new energy, thermal management, microwave absorption, and electromagnetic shielding. Graphene's porous structure, in particular, inherits graphene's high surface area and abundant pores while leveraging its high electrical and thermal conductivity, attracting significant attention in fields such as energy, catalysis, and composite materials.

[0003] Although porous graphene membranes have shown great potential in many applications due to their unique structure and properties, they still face some challenges in practical application. Graphene porous membranes prepared using graphene oxide as raw material often suffer from wide pore size distribution and poor compression rebound. This is because the removal rate of the abundant oxygen-containing groups on the graphene oxide surface is difficult to control. The rapid escape of a large amount of gas leads to the formation of large pore structures within the membrane. The appearance of large pores, in turn, causes the groups on the surrounding graphene sheets to be removed and escape from the large pores, further expanding the large pores and creating small pores around them. These large pores will undergo irreversible collapse during compression, thereby affecting the overall compressive strength and rebound properties of the material. In addition, due to the two-dimensional orientation characteristics of the graphene membrane, gas tends to escape along the horizontal direction of the membrane, resulting in a flat pore structure for most of the pores, which is also not conducive to compression performance. Summary of the Invention

[0004] In response to the problem that the current traditional preparation process is difficult to improve the compression rebound performance of graphene foam film, the present invention provides a preparation method of high-rebound graphene foam film. By adjusting the mixed solvent composition of the reducing agent, rapid reduction and foaming are suppressed, and a graphene foam film with a narrow pore size distribution and a small average pore size is prepared. It exhibits excellent compression rebound performance and can be used as an elastic skeleton in scenarios such as composite materials, thermal interface materials, and electrode materials.

[0005] Specifically, the present invention adopts the following technical solution: a method for preparing a high-resilience graphene foam film, comprising the following steps: (1) dissolving hydrazine hydrate in a mixed solvent of tert-butanol and water, wherein the mass ratio of hydrazine hydrate to the mixed solvent is 1 to 10:100, and the mass ratio of tert-butanol to water is 2 to 10:1; (2) Soaking the graphene oxide film in the mixed solution obtained in step (1) at 20-40°C for 10-30 minutes to obtain a foamed wet film; (3) drying the foamed wet film obtained in step (2), reducing it at a low temperature of 150-200°C for 10-24 h, then placing it in a nitrogen atmosphere, heating it at 5°C / min to 1300°C and keeping it at that temperature for 1-3 h, and then cooling it naturally to obtain a foamed carbonized film; (4) The foamed carbonized film obtained in step (3) is placed in an argon atmosphere, heated to 2000-2600 °C at 5 °C / min for high temperature treatment for 0.5-3 h, and then cooled to room temperature to obtain a high-resilience graphene foamed film.

[0006] Tert-butanol is a weakly polar molecule that has a weak effect on graphene oxide and can only partially swell graphene oxide. After tert-butanol and water are miscible, the overall polarity of the mixed solution decreases, resulting in limited free movement of graphene oxide sheets in the mixed solvent. In addition, the ability of hydrazine hydrate to contact graphene oxide also decreases, so that it cannot deform quickly during the foaming process to produce a large porous structure. In addition, due to the swelling effect, graphene oxide forms a wrinkled structure in the vertical direction, so that the gas no longer relies purely on the horizontal escape channel, and it is easy to form a pore structure that is closer to a circular shape (such as Figure 2 This narrow distribution and nearly circular pores have better compression resistance and rebound performance.

[0007] Furthermore, the thickness of the graphene oxide film in step (2) is between 10 and 100 μm. If the graphene oxide film is too thin, its own strength after foaming is too low and it is easy to break; if the film is too thick, the pores on the upper and lower surfaces will be larger due to the more thorough foaming reaction, and the pores will become smaller as they approach the center, resulting in uneven pores in the vertical direction.

[0008] Furthermore, the carbon-oxygen ratio of the graphene oxide film in step (2) is not greater than 15. Too high a carbon-oxygen ratio of graphene oxide cannot provide the oxygen-containing functional groups required for foaming, thereby affecting the foaming effect. Preferably, the carbon-oxygen ratio of the graphene oxide film in step (2) is 3.5-6.

[0009] Furthermore, the mass ratio of the graphene oxide membrane to the mixed solution in step (2) is not greater than 10%. Too much addition of the graphene oxide membrane and insufficient foaming agent will lead to insufficient reaction inside the membrane and uneven pore size distribution.

[0010] Furthermore, the graphene oxide film in step (2) is obtained by extruding or casting a graphene oxide slurry into a film and then drying it.

[0011] Furthermore, the drying method in step (3) is one or more combinations of natural air drying, infrared heating drying, and hot air drying.

[0012] Furthermore, the inert gas in step (3) is one of nitrogen and argon, or a mixture thereof.

[0013] Beneficial effects of the present invention: (1) Significantly improve the compression resilience of graphene foam film: By introducing low-polarity tert-butyl alcohol, on the one hand, the mobility of graphene oxide is reduced, and on the other hand, the ability of hydrazine hydrate to contact with graphene oxide is reduced, thus avoiding the problem of uneven pore size distribution inside the graphene film caused by rapid reduction of hydrazine hydrate, forming a fine pore structure, and improving the overall compression resistance and resilience of the material.

[0014] (2) Significantly improve the electrical and thermal conductivity of the material in the vertical direction: The internal pores of conventional foam films are mostly large-sized flat structures, and no effective network structure is built in the vertical direction. In contrast, the material obtained by the present invention constructs a more efficient three-dimensional vertical network, which has unique advantages in application scenarios such as thermal interfaces, sensors, and phase change energy storage.

[0015] (3) Simple operation: Adding a certain amount of tert-butanol to the conventional hydrazine hydrate reduction method makes the process easy to implement and the cost is controllable. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a low-magnification scanning electron microscope (SEM) image of a cross section of the material obtained in Example 1; Figure 2 This is a high-magnification scanning electron microscope (SEM) image of the cross section of the material obtained in Comparative Example 1; Figure 3 The pore size distribution diagram of Example 1 and Comparative Example 1 in the range of 10 to 2000 μm; Figure 4 is the compression-rebound curve of Example 1; Figure 5 This is the compression-rebound curve of Comparative Example 1. DETAILED DESCRIPTION

[0017] The embodiments of the present invention are further described below with reference to a number of embodiments.

[0018] It should be clear that the embodiments described are only part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0019] Unless otherwise specified, the raw materials used in the present invention are conventional commercial products; the methods used in the present invention are conventional methods in the art unless otherwise specified.

[0020] The terms used in the embodiments of the present application are for the purpose of describing specific embodiments only and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates otherwise. The terms "first" and "second" are used for descriptive purposes only and are not to be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, features defined as "first" and "second" may explicitly or implicitly include one or more of such features.

[0021] In the description of the present invention, “plurality” means two or more than two, unless clearly defined otherwise.

[0022] In the description of the present invention, it should be understood that the terms "longitudinal", "transverse", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "clockwise", "counterclockwise" and the like to indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0023] As is common knowledge in this field, the pore size is calculated by analyzing the SEM image using Image J software; the coefficient of dispersion refers to the ratio of the standard deviation to the mean; and the vertical thermal conductivity is tested using the laser flash method, using the German NETZSCH LFA467 equipment, and a vertical fixture for testing.

[0024] Example 1 (1) dissolving hydrazine hydrate in a mixed solvent of tert-butanol and water, wherein the mass ratio of hydrazine hydrate to the mixed solvent is 10:100, and the mass ratio of tert-butanol to water is 3:1; (2) Soaking a graphene oxide film with a thickness of 50 μm and a carbon-oxygen ratio of 3.5 in the mixed solution obtained in step (1), with the mass ratio of the graphene oxide film to the mixed solution being 1:100, at 20°C for 30 min to obtain a foamed wet film; (3) The foamed wet film obtained in step (2) was naturally air-dried, and then reduced at 150 °C for 24 h. Then, the film was placed in a nitrogen atmosphere, heated at 5 °C / min to 1300 °C and kept at that temperature for 1 h, and then cooled naturally to obtain a foamed carbonized film. (4) The foamed carbonized film obtained in step (3) was placed in an argon atmosphere, heated to 2000 °C at 5 °C / min for 3 h, and then cooled to room temperature to obtain a high-resilience graphene foamed film.

[0025] The microscopic morphology of the cross section of the obtained graphene foam film is as follows: Figure 1 and Figure 2 As shown in the figure, it can be found that the internal structure is a three-dimensional network structure formed by overlapping graphene sheets, which contains a large number of holes with relatively uniform sizes. The graphene sheets around the holes are connected to form a continuous structure. In contrast, the internal structure of the graphene membrane reduced with hydrazine hydrate is mainly flat pores with uneven sizes ( Figure 2 ). Figure 3 The pore size distribution of Example 1 and Comparative Example 1 in the range of 10 to 130 microns is shown in Figure 1. The pore size distribution dispersion coefficient of Example 1 is 0.57, and that of Comparative Example 1 is 0.81, which proves that the pore size distribution of Example 1 is more uniform. Figure 4 As shown in the graphite graphite sheet, under 50% strain compression, the irreversible compression is approximately 6%, demonstrating high compression resilience. In comparison, the graphene film reduced with hydrazine hydrate has an irreversible compression of 26%, indicating poor shape recovery after compression. The resulting graphene foam film has a perpendicular thermal conductivity of 67 W / m K, higher than that of Comparative Example 1 (25 W / m K).

[0026] Example 2 (1) dissolving hydrazine hydrate in a mixed solvent of tert-butanol and water, wherein the mass ratio of hydrazine hydrate to the mixed solvent is 20:100, and the mass ratio of tert-butanol to water is 2:1; (2) Immerse a graphene oxide film with a thickness of 10 μm and a carbon-oxygen ratio of 3.5 in the mixed solution obtained in step (1), wherein the mass ratio of the graphene oxide film to the mixed solution is 1:100, and maintain the mixture at 20°C for 20 min to obtain a foamed wet film; (3) The foamed wet film obtained in step (2) was naturally air-dried, and then reduced at 150 °C for 24 h. Then, the film was placed in a nitrogen atmosphere, heated at 5 °C / min to 1300 °C and kept at that temperature for 1 h, and then cooled naturally to obtain a foamed carbonized film. (4) The foamed carbonized film obtained in step (3) was placed in an argon atmosphere, heated to 2000 °C at 5 °C / min for 3 h, and then cooled to room temperature to obtain a high-resilience graphene foamed film.

[0027] The obtained graphene foam film has a pore size distribution dispersion coefficient of 0.64 in the range of 10-130 microns. Under 50% strain compression, its irreversible compression is about 10%, and its vertical thermal conductivity is 58 W / m K.

[0028] Example 3 (1) dissolving hydrazine hydrate in a mixed solvent of tert-butanol and water, wherein the mass ratio of hydrazine hydrate to the mixed solvent is 1:100, and the mass ratio of tert-butanol to water is 3:1; (2) Immerse a graphene oxide film with a thickness of 10 μm and a carbon-oxygen ratio of 3.5 in the mixed solution obtained in step (1), wherein the mass ratio of the graphene oxide film to the mixed solution is 1:100, and maintain the mixture at 40°C for 10 min to obtain a foamed wet film; (3) The foamed wet film obtained in step (2) was dried by infrared heating, and reduced at a low temperature of 200 °C for 24 h. Then, the film was placed in an argon atmosphere, heated at 5 °C / min to 1300 °C and kept at that temperature for 1 h, and then cooled naturally to obtain a foamed carbonized film. (4) The foamed carbonized film obtained in step (3) was placed in an argon atmosphere, heated to 2000 °C at 5 °C / min for 3 h, and then cooled to room temperature to obtain a high-resilience graphene foamed film.

[0029] The obtained graphene foam film has a pore size distribution dispersion coefficient of 0.46 in the range of 10-130 microns. Under 50% strain compression, its irreversible compression is about 5%, and its vertical thermal conductivity is 73 W / m K.

[0030] Example 4 (1) dissolving hydrazine hydrate in a mixed solvent of tert-butanol and water, wherein the mass ratio of hydrazine hydrate to the mixed solvent is 20:100, and the mass ratio of tert-butanol to water is 2:1; (2) Soaking a graphene oxide film with a thickness of 100 μm and a carbon-oxygen ratio of 6 in the mixed solution obtained in step (1), with the mass ratio of the graphene oxide film to the mixed solution being 1:100, at 20°C for 30 min to obtain a foamed wet film; (3) The foamed wet film obtained in step (2) was dried by infrared heating, and reduced at a low temperature of 200 °C for 10 h. Then, the film was placed in a nitrogen atmosphere, heated at 5 °C / min to 1300 °C and kept at this temperature for 3 h, and then cooled naturally to obtain a foamed carbonized film. (4) The foamed carbonized film obtained in step (3) was placed in an argon atmosphere, heated to 2600 °C at 5 °C / min for 0.5 h, and then cooled to room temperature to obtain a high-resilience graphene foamed film.

[0031] The obtained graphene foam film has a pore size distribution dispersion coefficient of 0.66 in the range of 10-130 microns. Under 50% strain compression, its irreversible compression is about 8%, and its vertical thermal conductivity is 62 W / m K.

[0032] Comparative Example 1 (1) Dissolve hydrazine hydrate in water, wherein the mass ratio of hydrazine hydrate to water is 10:100; (2) Soaking the graphene oxide film in the mixed solution obtained in step (1) and maintaining it at 20°C for 30 minutes to obtain a foamed wet film; (3) The foamed wet film obtained in step (2) was naturally air-dried, and then reduced at 150 °C for 24 h. Then, the film was placed in a nitrogen atmosphere, heated at 5 °C / min to 1300 °C and kept at that temperature for 1 h, and then cooled naturally to obtain a foamed carbonized film. (4) The foamed carbonized film obtained in step (3) was placed in an argon atmosphere, heated to 2000 °C at 5 °C / min for 3 h, and then cooled to room temperature to obtain a graphene foamed film.

[0033] The compression rebound curve of the obtained graphene foam film is as follows: Figure 5 As shown in Figure 3, under 50% strain compression, its irreversible compression is about 27%, indicating that its ability to recover shape after compression is poor.

Claims

1. A method for preparing a high-resilience graphene foam film, characterized in that: The following steps are involved: (1) dissolving hydrazine hydrate in a mixed solvent of tert-butyl alcohol and water, wherein the mass ratio of hydrazine hydrate to the mixed solvent is 1-10:100, and the mass ratio of tert-butyl alcohol to water is 2-10:1; (2) Soaking the graphene oxide film in the mixed solution obtained in step (1) at 20-40° C. for 10-30 min to obtain a foamed wet film; (3) drying the foamed wet film obtained in step (2), reducing it at a low temperature of 150-200°C for 10-24 h, then placing it in an inert gas atmosphere, heating it to 1300°C at a rate of 5°C / min and keeping it at that temperature for 1-3 h, and cooling it naturally to obtain a foamed carbonized film; (4) The foamed carbonized film obtained in step (3) is placed in an argon atmosphere, heated to 2000-2600°C at 5°C / min for high temperature treatment for 0.5-3 h, and then cooled to room temperature to obtain a high-resilience graphene foamed film.

2. The preparation method according to claim 1, characterized in that: The thickness of the graphene oxide film in step (2) is between 10 and 100 μm.

3. The preparation method according to claim 1, characterized in that: The carbon-oxygen ratio of the graphene oxide film in step (2) is not greater than 15.

4. The preparation method according to claim 3, characterized in that: The carbon-oxygen ratio of the graphene oxide film in step (2) is 3.5-6.

5. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the graphene oxide film to the mixed solution is not greater than 10%.

6. The preparation method according to claim 1, characterized in that: The graphene oxide film in step (2) is obtained by extruding or casting a graphene oxide slurry and then drying it.

7. The preparation method according to claim 1, characterized in that: The drying method in step (3) is one or more combinations of natural air drying, infrared heating drying, and hot air drying.

8. The preparation method according to claim 1, characterized in that: The inert gas in step (3) is one of nitrogen and argon, or a mixture thereof.

Citation Information

Patent Citations

  • Preparation method of activated foam carbon for supercapacitor electrode material

    CN110980727A

  • Amidated graphene aerogel as well as preparation method and application thereof

    CN112624092A

  • Graphene foam film and preparation method thereof

    CN116924800A

  • Preparation method of graphene foam film with high thermal conductivity and high flexibility

    CN118206109A

  • Method for preparing graphite three-dimensional heat-conducting filler with assistance of graphene oxide

    CN118515273A

Cited By

  • Preparation method of graphene interface material

    CN121269692A